2015
DOI: 10.1101/029868
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting quantitative traits from genome and phenome with near perfect accuracy

Abstract: In spite of decades of linkage and association studies and its potential impact on human health, reliable prediction of an individual's risk for heritable disease remains difficult. Large numbers of mapped loci do not explain substantial fractions of heritable variation, leaving an open question of whether accurate complex trait predictions can be achieved in practice. Here, we use a genome sequenced population of B7,000 yeast strains of high but varying relatedness, and predict growth traits from family infor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 37 publications
(39 reference statements)
1
12
0
Order By: Relevance
“…As a direct consequence of the experimental design, each POL shares one haploid genome with siblings spawned from the same haploid parent. This sharing of half a genome had surprisingly large effects on trait similarity, greatly aiding both trait prediction from relatives 23 and the partitioning of trait variation into its additive, dominant and epistatic components. In contrast, it somewhat restricted our ability to distinguish the weaker effects of individual loci and the calling of those QTLs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a direct consequence of the experimental design, each POL shares one haploid genome with siblings spawned from the same haploid parent. This sharing of half a genome had surprisingly large effects on trait similarity, greatly aiding both trait prediction from relatives 23 and the partitioning of trait variation into its additive, dominant and epistatic components. In contrast, it somewhat restricted our ability to distinguish the weaker effects of individual loci and the calling of those QTLs.…”
Section: Discussionmentioning
confidence: 99%
“…1a). This sharing of half a genome accounted for surprisingly much of the overall variation in traits 23 , which somewhat restricted our capacity to distinguish contributions from individual alleles and allele pairs from the effect of the genetic background. Nevertheless, our platform provided a cost-efficient framework for calling both additive and nonadditive (dominance and epistasis) QTLs in diploid models.…”
Section: Cost-efficient Qtl Mapping In Yeast Pol Diploid Hybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…This throughput is orders of magnitude better than what can be achieved by liquid microcultivation. In recent proof-of-principle studies, we have illustrated the importance of simultaneous high-resolution and high throughput analysis, using Scan-o-matic to completely decompose trait variation in diploids into its dominant, epistatic, and additive components , and to predict traits of individuals with near perfect accuracy from their genome and the genome and phenome of relatives (Martens et al 2016). Here, we showed that Scan-o-matic nicely captures the known salt biology of S. cerevisiae, largely uncovering the same cellular functions as earlier found to be important by microcultivation .…”
Section: Discussionmentioning
confidence: 99%
“…As a case in point, the most accurate prediction of gene expression levels is currently made from a broad set of epigenetic features using sparse linear models (Karlic et al , ; Cheng et al , ) or random forests (Li et al , ); how the selected features determine the transcript levels remains an active research topic. Predictions in genomics (Libbrecht & Noble, ; Märtens et al , ), proteomics (Swan et al , ), metabolomics (Kell, ) or sensitivity to compounds (Eduati et al , ) all rely on machine learning approaches as a key ingredient.…”
Section: Introductionmentioning
confidence: 99%